2013
DOI: 10.1002/phy2.90
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MMP-7 increases collagen 1A2 in the aging kidney

Abstract: The percentage of the U.S. population over 65 is rapidly increasing, as is the incidence of chronic kidney disease (CKD). The kidney is susceptible to age-dependent alterations in structure, specifically tubulointerstitial fibrosis that leads to CKD. Matrix metalloproteinases (MMPs) were initially characterized as extracellular matrix (ECM) proteinases; however, it is clear that their biological role is much larger. We have observed increased gene expression of several MMPs in the aging kidney, including MMP-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 59 publications
1
27
0
7
Order By: Relevance
“…Of the members of the Src kinase family, we have reported that mechanical stretch activates c-Src and enhances the activation of ERK1/2 in renal proximal tubular cells (1). Moreover, a variety of experimental studies implicate c-Src in the pathogenesis of progressive renal fibrosis (27,29,45). Additionally, numerous studies indicate that c-Src is critical for TGF-␤1-mediated renal fibrosis (7,23,48).…”
Section: Discussionmentioning
confidence: 99%
“…Of the members of the Src kinase family, we have reported that mechanical stretch activates c-Src and enhances the activation of ERK1/2 in renal proximal tubular cells (1). Moreover, a variety of experimental studies implicate c-Src in the pathogenesis of progressive renal fibrosis (27,29,45). Additionally, numerous studies indicate that c-Src is critical for TGF-␤1-mediated renal fibrosis (7,23,48).…”
Section: Discussionmentioning
confidence: 99%
“…Como descrito por Slusarz et al (2013), tal confirmação serve também para humanos, uma vez que a incidência de doenças renais em indivíduos norte americanos, aumentou, proporcionalmente ao aumento da população acima de 65 anos.…”
Section: Discussionunclassified
“…As alterações morfológicas que levam a lesão e doença renal em felinos senis, também são descritas para outras espécies, como em caninos e em humanos, de acordo respectivamente com Lustoza & Kogika (2003) e Slusarz et al (2013).…”
Section: Discussionunclassified
See 2 more Smart Citations